Penggunaan Metode JIGSAW Terhadap Minat Belajar Siswa Kelas V di SD Negeri 101900 Lubuk Pakam - Handayani, Ridha; Ritonga, Zon Saroha; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This study aims to analyze the impact of the jigsaw learning method on the learning interest of fifth-grade students at SDN 101900 Lubuk Pakam. The primary issue addressed in this research is the low student engagement, which necessitates innovative teaching methods to enhance learning interest. A qualitative approach was employed, with data collected through observation, interviews, and questionnaires completed by both students and teachers. The findings reveal that the implementation of the jigsaw method significantly improved students' learning interest. This is evidenced by an average student score of 78.4% (categorized as good) and a teacher score of 3.22%, equivalent to 80% (good). The jigsaw method was deemed effective as it fosters active interaction among students and boosts learning motivation. The study concludes that this method serves as a viable instructional strategy to enhance student engagement and interest, particularly at the elementary school level.